A research note on entrepreneurs' financial commitment and crowdfunding success. Issue 3 (3rd July 2018) - Löher, Jonas; Schneck, Stefan; Werner, Arndt
ABSTRACT: Established early stage investors decide to invest in new ventures after evaluating the propensity of success and the risk of failure. Consequently, it is of considerable importance that the founders invest substantial own financial means and are thus highly committed to business success. Despite its key role in practice, the entrepreneurs' own financial commitment has not yet been discussed in an equity crowdfunding context. Applying a signalling approach, our empirical findings show that entrepreneurs with comparatively more ex ante financial commitment in their venture achieve significantly higher funding success. Moreover, our results suggest that financial commitment is the single most important variable determining funding success.